Distribution of Marine debris in Coral Reef Ecosystems on Mules Island, Sawu Marine National Park - Idris Idris; Fakhrurrozi Fakhrurrozi; Desna Bagus Suhendar; Akbar Rochyadi; Rhojim Wahyudi; Chandrika Eka Larasati (Jurnal Biologi Tropis, 2023)
Mules Island and its surroundings are included in the Savu Sea National Park (TNP) area and administratively included in the Manggarai Regency, East Nusa Tenggara Province (NTT). The waters of the area have a high potential for coral reef ecosystem resources and are important support for the marine life. However, the current condition of anthropogenic pressure continues to increase due to an increase in the number of people living on the coast and small islands. One of the pressures that are currently a big issue is the existence of marine debris, where studies related to its impact and distribution on coral reef ecosystems are still very few. The purpose of this study was to determine the distribution and types of marine debris in the coral reef ecosystem on Nucamolas Island and its surroundings. Observations were made on 1-3 November 2021 at 12 stations. The research method used is the belt transect method with an area of 500 m2. Data collection was assisted by SCUBA diving equipment at a depth of 5-7 m on the coral reef flat. The results of this study found that the dominant marine debris in the coral reef ecosystem was organic waste (64.3%) and a group of macro debris (71,4%). Based on the type, the dominant species found were logs (37%), which physically damaged the coral, especially when currents and waves were moving. The distribution of marine debris at the study site was only found at 8 stations while the other 4 were not found.